Industrial Robot Accuracy Testing with QC20-W Ballbar Diagnostic System - Józwik, Jerzy; Kuric, Ivan; Ostrowski, Dawid; Dziedzic, Krzysztof (Manufacturing Technology Journal, 2016)
An important characteristic of industrial robots is their accuracy. It is of particularly importance in high-precision tasks, e.g. mounting or machining of elements. In order to meet the requested quality demands for products, as well as appropriate working conditions, it is absolutely essential to regularly inspect the technical condition of robots, e.g. their accuracy.The following paper aims at identification of accuracy errors of an industrial robot MOTOMAN HP20. The selected measuring method was the roundness test with the use of the telescopic, kinematic QC20W - Ballbar. The paper presents the methodology of experimental tests. The influence of the radius of the interpolation circle, as well as the influence of the set motion speed on the value of chosen accuracy errors was determined. The results were presented graphically and analysed.
Keywords: diagnostic; accuracy; robots; ballbar system